Wakalah contract in the investment from the perpective of Islamic law and its applications in Bahrain Islamic banks: An analysis / Salman Duaij Hamad Busaeed - Salman Duaij, Hamad Busaeed (2017)
This study is a practical and analytical study of the agency contract in the investment and its applications in the Bahraini Islamic banks. The study aimed to release the concept of agency contract in the investment considering that cash transactions in Islamic banks rely on it. In addition to clarifying the provisions of the agency contract in the investment, and to identify the role of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and the Fatwa and Sharia supervisory organizations in the agency contract in the investment, Identify models of modern applications to hold the agency to invest in Bahrain's Islamic banks. The study relied on inductive analytical approach so as to reach to the concept of the agency in Islamic jurisprudence and provisions, Also defining image of the agency contract in the investment and highlighted provisions that respect, and also used the descriptive and analytical approach to describe the applications relating to the holding in the investment agency. The study reached of many results . And The main results ware that: the agency contract at investment is acceptable contract based on Sharia, and this contract needful rather than other agency contracts. In addition, the role of AAOIFI appeared in issuing agency standard at investments and identified its main features for Islamic banks and Islamic financial institutes. Regarding to the role of Fatwa and Sharia supervisory organizations it mainly was in past and future controlling to the applications of Islamic banks for agency contract at investment. In conclusion, the study illustrated the main modern applications in Bahraini Islamic Banks for agency contract at investment and it represented by: the investment deposits, investment Instruments, International Murabaha contract, and Islamic Banks transactions with each other or with traditional banks – briefly, these applications are acceptable based on Sharia. Moreover, the study reached that, two forms of monetary applications in agency contract at investment are not acceptable according to Sharia.